Investigating children's chemical exposome – Description and possible determinants of exposure in the region of Luxembourg based on hair analysis. (July 2022) - Iglesias-González, Alba; Schweitzer, Mylène; Palazzi, Paul; Peng, Fengjiao; Haan, Serge; Letellier, Elisabeth; Appenzeller, Brice M.R.
Highlights: 153 chemicals (pesticides, PCBs, BDEs and bisphenols) were analysed in 264 children. 29 to 88 chemicals (median = 61) were detected per hair sample. Pollutants' concentration was higher in boys and in younger children's hair. Presence of POPs in most children's hair suggests that exposure is still ongoing. Exposure was associated with diet, residence area and presence of pets at home. Abstract: The specific physiology and behaviour of children makes them particularly vulnerable to chemical exposure. Specific studies must therefore be conducted to understand the impact of pollution on children's health. Human biomonitoring is a reliable approach for exposure assessment, and hair, allowing the detection of parent chemicals and metabolites, and covering wider time windows than urine and blood is particularly adapted to study chronic exposure. The present study aims at assessing chemical exposure and investigating possible determinants of exposure in children living in Luxembourg. Hair samples were collected from 256 children below 13 y/o and tested for 153 compounds (140 pesticides, 4 PCBs, 7 BDEs and 2 bisphenols). Moreover, anthropometric parameters, information on diet, residence, and presence of pets at home was collected through questionnaires. Correlations, regressions, t-tests, PLS-DA and MANOVAs, were used to investigate exposure patterns. Twenty-nine to 88 (median = 61) compounds were detected per sample. The highest median concentration was observed for BPA (133.6 pg/mg). Twenty-three biomarkers were detected in ≥ 95% of the samples, including 13 in all samples (11 pesticides, BPA and BPS). Exposure was higher at younger ages (R 2 = 0.57), and boys were more exposed to non-persistent pesticides than girls. Presence of persistent organic pollutants in most children suggests that exposure is still ongoing. Moreover, diet (e.g. imazalil: 0.33 pg/mg in organic, 1.15 pg/mg in conventional, p-value < 0.001), residence area (e.g. imidacloprid: 0.29 pg/mg in urban, 0.47 pg/mg in countryside, p-value = 0.03), and having pets (e.g. fipronil: 0.32 pg/mg in pets, 0.09 pg/mg in no pets, p-value < 0.001) were identified as determinants of exposure. The present study demonstrates that children are simultaneously exposed to multiple pollutants from different chemical classes, and confirms the suitability of hair to investigate exposure. These results set the basis for further investigations to better understand the determinants of chemical exposure in children.